Peningkatan Pengetahuan Kader Pkk Desa Sumpang Binangae Terhadap Kesehatan Ibu Bersalin - Riswanti, Riswanti; Asmin, Risna Yunita; Nurmiati, Nurmiati; Hadijah, Hadijah; Kamaruddin, Muh. Ihsan; Adiaksa, Baso Witman; Djunaedi, Djunaedi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
The program initiated by the Indonesian government has only one goal, namely to reduce maternal, infant and child mortality rates in Indonesia. However, in reality, maternal mortality rates have not been in accordance with the expected target. The main problem currently still being faced related to the health of pregnant women in Indonesia is the still high maternal mortality rate related to childbirth. The goal of PkM is to increase the knowledge of PKK cadres in Sumpang Binangae Village regarding maternal health. The method used in this community service is to provide education through counseling on health education to increase the knowledge of cadres, efforts to increase the knowledge of PKK cadres through counseling on the importance of supporting mothers during the childbirth process. The results of community service are an average posttest score of knowledge level of 8.65, there is an increase in PKK cadre knowledge regarding support for mothers in childbirth through counseling and assistance to PKK cadres of 1.29. The conclusion is that community service activities Providing IEC regarding support for mothers in childbirth on an ongoing basis can increase community knowledge regarding the importance of support for mothers during the childbirth process.